Chloroplast lipid biosynthesis - Benning, Christoph (Henry Stewart Talks, 2007)
Uniqueness of thylakoid membrane lipid composition, Nonphosphorous glycerolipids, Genetic analysis of lipid biosynthesis and function in Arabidopsis, Regulation of membrane lipid composition by phosphate availability, Biosynthesis of the plant sulfolipid, Function of anionic lipids in the photosynthetic membrane, Biosynthesis of galactoglycerolipids, Lipid trafficking between the chloroplast and other organelles, Regulation of lipid trafficking